Interactive effect of ambient and elevated levels of tropospheric ozone, nutrition and PGPR on growth and yield of chickpea (Cicer arietinum) - NEDUMARAN, SETHUPATHI; SHARMA, D K; BHATIA, ARTI; SHRIVASTAVA, MANOJ; SHIVAY, Y S; MOHAN, DEEPASRI; DINESH, G K; MURUGESAN, KOKILA; MAHADEVA, MANU SUNDAVALU (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2020 and 2021 at ICAR-Indian Agricultural Research Institute, New Delhi, to study the interactive effect of nutrient and PGPR (Plant growth promoting rhizobacteria) on growth and yield of chickpea (Cicer aeritinum L.) cv. Pusa 3043 under ambient and elevated levels of ozone in FAOE (Free air ozone enrichment). A loss of 15–16% in dry matter production was observed under elevated ozone (EO3) when compared to ambient ozone (AO3) conditions. Seed treatment with PGPR was found to compensate for this loss as an increase in seed yield 18–19% was observed over untreated seeds. In terms of seed yield, the PGPR treatments with 75% nitrogen showed significant improvement compared to the recommended dose of fertilizer (RDF) application. A yield increase of 12% and 14% was observed with PGPR like RPAN8 (Anabena laxa) and An-Rh (Anabena torulosa with Mesorhizobium ciceri) (chickpea rhizobium) respectively, suggesting an advantage of an–Rh over RPAN8 under EO3. A combination of both PGPRs outperformed the individual PGPR, showing a 19% yield increase over RDF. This proves the potential of seed treatment with PGPR (RPAN8 and An-Rh) in ameliorating tropospheric ozone-induced stress in chickpea plants.